Effect of Sand Particle Size and Concentration on Performance of Screen Filter in Trickle Irrigation - Thokal, R T; Raghavendra, A G; Suresh, N M; Anil Kumar, T D (Annals of Arid Zone, 2016)
Performance of screen filter with 100 mesh (150 !-.un) was evaluated with three sand particle sizes at two low sand concentrations. Smaller ratios of filter pore size to sand particle size caused greater accumulation of sand in the filter prior to reaching a predetermined head limit (40 KPa). Larger particles accumulated in the housing. whereas smaller particles clogged the pores. Increasing intluelll sand. concentrations also caused greater sand accumulation. An equation was developed to characterize screen filter clogging. It was used to construct a nomogram for predicting the operation of filter under various conditions. The schedule for filter cleaning was estimated from pressure drop-time nomogram, which is valid for 150 J.1m-screen filter with tlow rate of 6.75 L sÂ·l The filters need to be cleaned after 130 to I S5 minutes operation of trickle irrigation system, when the irrigation water contains 15 mg L-1 sand with ISO to 425 J.1m sancl particles. For 10' mg L-1 sand concentration in irrigation water, cleaning should be clone after every 90. 160 and 190 minutes of the system operation for the sand particle size of 355 to 425 J.1m, 180 to 355 J.1m and ISO to 180 J.1m, respectively.